Review of current ECG consumer electronics (pros and cons) - Hilbel, Thomas; Frey, Norbert (Journal of electrocardiology, 2023)
Background - Several wearable, medical-grade consumer ECG devices are now available and integrated into consumer electronics like multi sensor fitness watches and scales. Specific consumer ECGs can also come in the form of patches or thin sensor plates in credit card or other shapes. Watches with ECG capabilities are often multi vital sign sensor devices. The majority of these devices are usually connected to a mobile smartphone. However, there are pros and cons to their use. - Methods - We review here an exemplary selection of modern consumer ECG devices based on device type, recording method and the number of standard ECG channels derived. - Results - Single-channel consumer ECG devices such as Smart Watches can be useful for detecting and monitoring atrial fibrillation and flutter and other arrhythmias, as well as ectopic complexes. However, they are currently limited with respect to recording duration and information content (a single-channel or limb‑lead ECG having less diagnostic information than a 12‑lead ECG). While some non watch-based consumer ECG devices can now record all 6 limb leads to yield increased information, no consumer ECG devices can currently reliably detect ST-segment deviations, potentially indicating myocardial infarction or ischemic episodes. Moreover, barriers to use still exist for at-risk elderly people. Finally, there currently is no universal data exchange format. - Conclusion - Consumer ECG devices, whether in fitness or fashionable design, allow for reliable detection of atrial fibrillation. Timely detection of atrial fibrillation and subsequent treatment might protect against stroke, especially in high-risk groups, yet prospective evidence is still lacking. Six-channel consumer ECG and longer data collection capabilities extend potential functionality, including for the monitoring of ST-segments and QT intervals. However, no currently available devices are sufficiently suitable for the detection of myocardial infarction or ischemia, which is why portable 12-channel technologies are desirable. For the reliable detection of a myocardial infarction, the determination of specific myocardial infarction blood markers and evaluation of patient medical history still is indispensable in addition to the 12 lead ECG.